Insulin action on the human placental endothelium in normal and diabetic pregnancy - Hiden, Ursula; Lang, Ingrid; Ghaffari-Tabrizi, Nassim; Gauster, Martin; Lang, Uwe; Desoye, Gernot (Current vascular pharmacology, 2009)
The placental endothelium is unique among the entire human vasculature. The blood enriched in oxygen and nutrients is transported in the veins, whereas the arteries contain deoxygenated blood coming from the fetus. The placental vasculature has to develop rapidly to ensure adequate supply of the fetus. Therefore, factors present in the fetal circulation will stimulate placental angiogenesis. In the third trimester of pregnancy the placental endothelium is richly endowed with insulin receptors. In a pregnancy complicated by maternal diabetes, fetal hyperinsulinemia resulting from maternal and, hence, fetal hyperglycaemia induces changes in the placental vasculature such as increased growth and angiogenesis. This review will discuss general effects of insulin on endothelial cells and further focus on insulin effects on the placental endothelium. Isolation and culture of placental endothelial cells has allowed the identification of insulin effects in vitro. These include metabolic effects of insulin i.e. stimulation of glycogen synthesis, and modulation of angiogenesis on the placental arterial endothelium i.e. regulation of ephrin-B2 expression, an arterial specific signalling molecule implicated in sprouting. The effect of insulin on ephrin-B2 in placental arterial endothelial cells as well as their particularly high expression levels of insulin receptors and receptors for vascular endothelial growth factors indicate that placental angiogenesis is likely to emanate from the arterial compartment and is stimulated by insulin.